Audit Delay in Property and Real Estate Companies: Evidence from the Pre and Post Pandemic Period - Elon Manurung; Ida Musdafia Ibrahim; Muhamad Rafi (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
This study aims to examine the effect of profitability, solvency, and firm size on audit delay in manufacturing companies in the property and real estate subsector listed on the Indonesia Stock Exchange during the 2019-2023 period. This research adopts a quantitative approach using secondary data obtained from annual financial statements and independent auditor reports. The population consists of all manufacturing companies in the property and real estate subsector listed on the Indonesia Stock Exchange. Purposive sampling was employed, resulting in 16 sample firms with a total of 80 panel data observations. Data analysis was conducted using panel data regression with the common effect model, supported by descriptive statistical analysis, classical assumption tests, and hypothesis testing using eviews 12 software. The results indicate that profitability and firm size have a negative and significant effect on audit delay, while solvency has a positive and significant effect. The novelty of this study lies in the use of an observation period covering the pre-pandemic, pandemic, and post-pandemic phases, as well as its specific focus on the property and real estate subsector, which is characterized by high asset intensity and audit risk. These findings provide theoretical implications by reinforcing agency theory and signaling theory, as well as practical implications for corporate management in improving the timeliness of audited financial reporting. Abstrak - Penelitian ini bertujuan untuk menganalisis pengaruh profitabilitas, solvabilitas, dan ukuran perusahaan terhadap audit delay pada perusahaan manufaktur subsektor properti dan real estate yang terdaftar di Bursa Efek Indonesia periode 2019-2023. Penelitian ini menggunakan pendekatan kuantitatif dengan data sekunder berupa laporan keuangan tahunan dan laporan auditor independen. Populasi penelitian mencakup seluruh perusahaan manufaktur subsektor properti dan real estate yang terdaftar di Bursa Efek Indonesia, dengan teknik pengambilan sampel menggunakan purposive sampling. Berdasarkan kriteria yang ditetapkan, diperoleh 16 perusahaan sebagai sampel penelitian dengan total 80 observasi data panel. Analisis data dilakukan menggunakan regresi data panel dengan common effect model, didukung oleh uji statistik deskriptif, uji asumsi klasik, serta pengujian hipotesis menggunakan perangkat lunak eviews 12. Hasil penelitian menunjukkan bahwa profitabilitas dan ukuran perusahaan berpengaruh negatif terhadap audit delay, sedangkan solvabilitas berpengaruh positif terhadap audit delay. Novelty penelitian ini terletak pada penggunaan periode pengamatan yang mencakup fase sebelum, selama, dan setelah pandemi COVID-19 serta fokus pada subsektor properti dan real estate yang memiliki karakteristik aset dan risiko audit yang tinggi. Temuan ini memberikan implikasi teoritis dalam memperkuat teori keagenan dan teori sinyal, serta implikasi praktis bagi manajemen perusahaan dalam meningkatkan ketepatan waktu pelaporan keuangan.